Comparison of Entities in Excerpts from the Novel Perahu Kertas and Its Translation Paper Boats - Nasution, Dea Yuanita; Ningsih, Harni Kartika (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
A text is a product of the cognitive representation of its producer, including literary and translation texts. To identify the influence of this cognitive background, this research aims to explore shifts in the field of experience in the translation of novels by identifying participants constructing the field. The study utilizes a qualitative method with the IDEATION framework from Systemic Functional Linguistics, specifically taxonomic relations theory. A parallel corpus is used, extracted from excerpts of the Indonesian novel "Perahu Kertas" and its English translation titled "Paper Boats." The investigation is conducted using the AntConc software as a corpus processing instrument. The data for this research includes nouns categorized into concrete, abstract, and metaphoric entities. The results reveal two crucial findings. Firstly, everyday concrete entities dominate in both data. Secondly, there is a shift in the translation process of selected nouns, indicated by differences in the types and frequencies of entities between the two datasets. Besides the differences in the field of experience backgrounds of each text producer and the use of translation procedures, the two findings also suggest systematic differences in each language that influence the translator’s choices and decisions underlying these shifts. This research provides a deeper understanding of the translation process and its impact on the representation of entities in the literary context Kata kunci: entitas, field of experience, korpus, taxonomic relations.